2010
DOI: 10.1186/1743-8977-7-37
|View full text |Cite
|
Sign up to set email alerts
|

Impact of agglomeration state of nano- and submicron sized gold particles on pulmonary inflammation

Abstract: BackgroundNanoparticle (NP) toxicity testing comes with many challenges. Characterization of the test substance is of crucial importance and in the case of NPs, agglomeration/aggregation state in physiological media needs to be considered. In this study, we have addressed the effect of agglomerated versus single particle suspensions of nano- and submicron sized gold on the inflammatory response in the lung. Rats were exposed to a single dose of 1.6 mg/kg body weight (bw) of spherical gold particles with geomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(114 citation statements)
references
References 42 publications
7
107
0
Order By: Relevance
“…Since both diffusion and sedimentation are influenced by agglomeration, the latter is expected to have a major impact on the NP uptake and toxicity 169 . It is important to note the difference between agglomeration and aggregation since both terms are often mixed up: aggregates are formed by covalent bonds and are therefore not as easy to break up as agglomerates, which are held together by van der Waals forces, hydrophobic interactions and/or hydrogen-bonds 170 . The formation of agglomerates originates from the pursuit of a state with a lower free surface energy and is strongly promoted by the hydrophobic nature of most NP 154,170 .…”
Section: The Effect Of Particle Agglomeration and Sedimentationmentioning
confidence: 99%
“…Since both diffusion and sedimentation are influenced by agglomeration, the latter is expected to have a major impact on the NP uptake and toxicity 169 . It is important to note the difference between agglomeration and aggregation since both terms are often mixed up: aggregates are formed by covalent bonds and are therefore not as easy to break up as agglomerates, which are held together by van der Waals forces, hydrophobic interactions and/or hydrogen-bonds 170 . The formation of agglomerates originates from the pursuit of a state with a lower free surface energy and is strongly promoted by the hydrophobic nature of most NP 154,170 .…”
Section: The Effect Of Particle Agglomeration and Sedimentationmentioning
confidence: 99%
“…The length and fiber diameter of each CNT itself (#1: no information; #2: mean length of 3.5 μm, fiber diameter of 30 nm, #3: mean length of 4.51 μm, fiber diameter of 150 nm, #4: mean length of 3.0 μm, fiber diameter of 10-15 nm, #5: mean length of 3.3 μm, fiber diameter of 40-50 nm) seem not to correlate with the extent of toxicity of its agglomerates in this study. The biological responses to nanoparticles reportedly depend on the dimensions and concentrations of the nanoparticle agglomerates (Gosens et al, 2010;Noël et al, 2012Noël et al, , 2013. Furthermore, recent reports have suggested that it is not only the size but also the shape that determines the extent of the toxicity (Bhattacharjee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Gosens et al [47] administered a single dose of 1.6 mg/kg bw of single (50 nm) and agglomerated (250 nm) gold particles in the rat lung by intratracheal instillation. Findings showed that both single and agglomerated particles were taken up by macrophages.…”
Section: Phagocytosis Of Nps and Inflammationmentioning
confidence: 99%